Informal Learning and its Moderating Effect Between Employability and job performance of Young Recent Graduates in Their First job - Medroa Delgado, Giancarlo (2024)
The purpose of this paper is to examine the effects of knowledge management through informal learning on the relationship between employability and job performance of recent graduates in their first jobs. A quantitative, cross-sectional survey of 392 graduates of business school management programs at 4 universities in Lima, Peru was conducted to study the relationship between employability and job performance as moderated by informal learning inside and outside the work environment. It is confirmed that informal learning positively moderates the relationship between employability and job performance of recent graduates. However, informal learning impacts the employability dimensions differently. The results challenge traditional methods of learning and training inside and outside the work environment and provide new insights for knowledge management, talent management and their induction, training and development programs for a dynamic workforce with digital skills developed since the university stage. The implications of limiting employees' access to informal learning activities may limit future employability and job performance; employees can develop knowledge and competencies through informal learning activities on their own initiative, however, it is important to facilitate this process within the organization's processes. This study provides further evidence of the relationships between employability, informal learning and job performance in young recent graduates. In addition, it provides knowledge on how business schools can include informal or non-instructional learning activities in their curricula, thus generating self-learning skills for upcoming graduates and improving their skills and competencies. © 2024 Academic Conferences Limited. All rights reserved.